Public Official Perception of Digital Human Resource Management in Karanganyar, Indonesia - Putri Chairani, Deswita; Nugroho, Rino; Wallang, Muslimin (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2025)
This study investigates user perceptions of Digital Human Resource Management through the MySAPK application in Karanganyar, Indonesia, using the Unified Model of Electronic Government Adoption (UMEGA). UMEGA includes seven key variables: performance expectancy, effort expectancy, social influence, facilitating conditions, perceived risk, user attitude, and behavioral intention. The study adopts a quantitative, associative research approach, employing a survey method with a structured questionnaire for data collection. The sample consists of 124 civil servants (ASN) in Karanganyar Regency who actively use the MySAPK application. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 3.0. The results reveal that effort expectancy, social influence, and user attitudes significantly influence ASN perceptions and behavioral intentions toward MySAPK. In contrast, performance expectancy, facilitating conditions, and perceived risk do not significantly affect users’ behavioral intentions. Furthermore, user attitude is a mediating variable, successfully transmitting the influence of social influence and effort expectancy on behavioral intention. This study contributes to the growing literature on digital government adoption by offering empirical evidence from a local Indonesian context, highlighting the behavioral dynamics influencing civil servant engagement with digital HRM tools. The findings underscore the urgency for public sector organizations to provide reliable digital infrastructure and foster positive user attitudes and supportive environments to enhance adoption. Policymakers and system developers are advised to focus on usability, social reinforcement, and user engagement strategies to ensure the successful and sustainable implementation of digital HRM systems like MySAPK.